2020
DOI: 10.1177/0306624x20919712
|View full text |Cite
|
Sign up to set email alerts
|

Situational Crime Prevention in Sexual Offenses Against Women: Offenders Tell Us What Works and What Doesn’t

Abstract: This study examined the perceived effectiveness of situational crime prevention (SCP) in sexual assault as rated by 140 offenders convicted for sex offenses against women in Australia. Participants were presented with three scenarios and asked to rate the perceived effectiveness of SCP techniques relating to guardianship, victim self-protective behavior, and crime prevention through environmental design (CPTED). Results indicate that the effectiveness of SCP methods was perceived to vary across different conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Situational crime prevention strategies can potentially reduce immediate offending opportunities that are arising from school closures (32,33). Situational crime prevention strategies consider key environmental factors that are associated with offending opportunities, and design prevention measures that restrict opportunities, whilst also increasing the risks of offending and limiting the benefits (33)(34)(35).…”
Section: Protecting Children: Situational Crime Preventionmentioning
confidence: 99%
“…Situational crime prevention strategies can potentially reduce immediate offending opportunities that are arising from school closures (32,33). Situational crime prevention strategies consider key environmental factors that are associated with offending opportunities, and design prevention measures that restrict opportunities, whilst also increasing the risks of offending and limiting the benefits (33)(34)(35).…”
Section: Protecting Children: Situational Crime Preventionmentioning
confidence: 99%
“…Situational crime prevention strategies can potentially reduce immediate offending opportunities that are arising from school closures ( 32 , 33 ). Situational crime prevention strategies consider key environmental factors that are associated with offending opportunities, and design prevention measures that restrict opportunities, whilst also increasing the risks of offending and limiting the benefits ( 33 – 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recent work indicates that these techniques are promising in the Global South in helping the police to solve serial offences [23,24]. While the use of BCL is the focus of this paper in terms of understanding how the information collected by witnesses could be used for the purposes of behavioural analysis, it is also worth noting that information about offending behaviour can also be used in other ways, such as implementing situational crime prevention strategies to protect communities [25], which uses offence data to identify high-risk circumstances and determine preventative measures that may limit crime opportunities [26]. Mobile applications have previously been piloted in Kenya to gather data for situational crime prevention purposes with some success [8]; for instance, Oduor et al (2014) found good will among the population to using apps to report crimes anonymously.…”
Section: Mobapp and Behavioural Analysismentioning
confidence: 99%